REFLEKSI PSIKOLOGI MUSIK DALAM PERILAKU MASYARAKAT SEHARI-HARI - Iswandi, Iswandi (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2015)
Music is a branch of art close to and present in human’s life every day. Through the social study perspective, this kind of concentration is usually called musical semiology or how music functions as an art creation in the society. In the daily life, men always listen to music intentionally or unintentionally. Therefore, music is inseparable from human life. The logical consequence is an effort to improve the role of music in the society, along with the fast development of media technology and culture. Art as a human creation has various functions which are not only for artistic interests. From the psychological context, music functions in and influence the increase of intelligence, therapeutic benefit that are not detached with its cultural, technical, and methodical background. Here, as part of the hybrid between music and psychology, musical therapy adopts relevant psychoterapic techniques. The term musical therapy has also been used in the curriculum of educational institution and foundation for children with specific needs of education with qualification of education or psychology for the specific needs.